Addressing personal parental values in decisions about childhood vaccination: Measure development. Issue 38 (10th September 2019) - Cataldi, Jessica R.; Sevick, Carter; Pyrzanowski, Jennifer; Wagner, Nicole; Brewer, Sarah E.; Narwaney, Komal J.; Shoup, Jo Ann; Resnicow, Ken; Glanz, Jason; Dempsey, Amanda; Kwan, Bethany M.
Highlights: The Parental Vaccine Values (PVV) scale measures vaccination-specific values. The PVV subscales are valid and internally consistent. Vaccine values were associated with vaccine attitudes, hesitancy, and behavior. Tailoring vaccine promotion messages to vaccine values may improve effectiveness. Abstract: Objective: Evidence-based strategies to address vaccine hesitancy are lacking. Personal values are a measurable psychological construct that could be used to deliver personalized messages to influence vaccine hesitancy and behavior. Our objectives were to develop a valid, reliable self-report survey instrument to measure vaccine values based on the Schwartz theory of basic human values, and to test the hypothesis that vaccine values are distinct from vaccine attitudes and are related to vaccine hesitancy and behavior. Methods: Parental Vaccine Values (PVV) scale items were generated using formative qualitative research and expert input, yielding 24 items for testing. 295 parents of children aged 14–30 months completed a self-report survey with measures of Schwartz's global values, the PVV, vaccine attitudes, and vaccine hesitancy. Factor analysis was used to determine vaccine values factor structure. Associations between vaccine values, vaccine attitudes, vaccine hesitancy, and vaccination behavior were assessed using linear and logistic regression models. Late vaccination was assessed from electronic medical records. Results: A six-factor structure for vaccine values was determined with good fit (RMSEA = 0.07, Bentler's CFI = 0.91) with subscales for Conformity, Universalism, Tradition, Self-Direction, Security- Disease Prevention, and Security- Vaccine Risk. Vaccine values were moderately associated with Schwartz global values and vaccine attitudes, indicating discriminant validity from these constructs. Multivariable linear regression showed vaccine hesitancy was associated with vaccine values Conformity (partial R 2  = 0.10) and Universalism (0.04) and vaccine attitudes Vaccine Safety (0.52) and Vaccine Benefit (0.16). Multivariable logistic regression showed that late vaccination was associated with vaccine value Self-direction (OR = 1.80, 95% CI: 1.26–2.65) and vaccine attitude of Vaccine Benefit (OR = 0.44, 95% CI: 0.32–0.60). Conclusions: The PVV scale had good psychometric properties and appears related to but distinct from Schwartz global values and vaccine attitudes. Vaccine values are associated with vaccine hesitancy and late vaccination and may be useful in tailoring future interventions.